2009
DOI: 10.1007/bf03179213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glutaminase-producing lactic acid bacteria isolated from Nham, a traditional Thai fermented food and characterisation of glutaminase activity of isolatedWeissella cibaria

Abstract: Five glutaminase-producing lactic acid bacteria were isolated from Nham, a Thai fermented pork sausage. Weisella cibaria (MSS1, MSS2, MSS3, and MBP5) and Leuconostoc citreum (MHV2) were identified by carbohydrate metabolism tests and 16S rDNA sequence -based phylogenetic analysis. Of these, W. cibaria MSS2 had the highest glutaminase activity (0.0085 U/mg) among them. The specific activity of glutaminase (0.024 U/mg) was obtained in static culture at 20 C using the modified MRS medium in which sucrose was subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…These results suggested that optimum L-glutaminase activity is varied from pH 6.0-9.0 and temperature at 27-40 ºC depends on the isolation source. The earlier study related to glutaminase producing bacteria from Thai food by Thongsanit et al (2009) suggested that food isolate of Weisella cibaria can able to produce 0.0085 u/mg of enzyme whereas the present study have reported that LAB isolate can produce 7.46 u/ mg of enzyme. …”
Section: Kinetics Of Growth and Glutaminase Productioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These results suggested that optimum L-glutaminase activity is varied from pH 6.0-9.0 and temperature at 27-40 ºC depends on the isolation source. The earlier study related to glutaminase producing bacteria from Thai food by Thongsanit et al (2009) suggested that food isolate of Weisella cibaria can able to produce 0.0085 u/mg of enzyme whereas the present study have reported that LAB isolate can produce 7.46 u/ mg of enzyme. …”
Section: Kinetics Of Growth and Glutaminase Productioncontrasting
confidence: 75%
“…cremoris are reported to produce glutaminase (Kieronczyk et al, 2001;Weingand-Ziadé et al, 2003). Thongsanit et al (2009) (Lin et al, 1995;Sanders et al, 1998;Cotter et al, 2001). GAD of Lactobacillus brevis and L. paracasei are biochemically well characterized (Hiraga et al, 2008;Komatsuzaki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Weissella cibaria could also play an important role in meat fermentation. Thongsanit et al (2009) proposed W. cibaria MSS2 as starter culture for the production of nham fermented sausage and for kimchi, due to the capacity of these bacteria to produce glutaminase, which is indispensable in food processing. Furthermore, the use of W. cibaria as starter for food fermentations promoted the formation of ornithine from arginine, which in turn may have beneficial health effects, such as anti-obesity effect due to high levels of ornithine in fermented foods ( Yu et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…They had been widely discovered from fermented foods such as cheese, kimchi, and soy sauce, and made great contributions to the flavor and taste ( Nguyen et al, 2013 ). Leuconostoc citreum had been reported to exhibit glutaminase-producing activity in a traditional Thai fermented food ( Thongsanit et al, 2009 ). Tetragenococcus halophilus was also proven to improve the flavor of fish sauce and increase the umami taste in soy sauce ( Udomsil et al, 2011 ; Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%